Mechanochemical synthesis of MnBi/Fe3C@C exchange coupled hard magnetic nanocomposites - Anuraag N.S.; Shaw S.K.; Upadhyay C.; Prasad N.K. (My University, 2025)
Despite the better suitability of rare earth permanent magnets for various applications, the scarcity of rare earths limits their application range. The, low temperature phase of MnBi is sought as a probable gap magnet without any rare earth elements. Further, the nanocomposites (soft/hard magnets) are known to provide better properties. In this study, Mn55Bi45/Fe3C@C nanocomposites with enhanced magnetic properties were prepared using cryogenic ball milling. The feasibility of utilizing Fe3C@C as a soft phase in hard-soft composites was explored. Fe3C@C was synthesized through the solvothermal technique, followed by calcination, resulting in a remarkable saturation magnetization (MS) of 150 emu/g. Different amounts of Fe3C@C (0, 5, 10, 15, and 20 wt.%) were added to Mn55Bi45 powder, and after cryo-milling, it was observed that the addition of 10 wt. % yielded the optimum results, with a 37% enhancement in MS and 58% increase in Mr values. The presence of exchange-coupled nanocomposites was confirmed through x-ray diffraction, transmission electron microscopy, and magnetic studies. This study not only paves the way for increasing the energy product of the MnBi system but also explores the potential of utilizing Fe3C@C as a soft phase—a relatively oxidation-resistant phase—in other hard magnetic systems. © 2023 Elsevier Inc.